2019
DOI: 10.1002/aelm.201900975
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Dipole Coupling in 2D van der Waals Ferroelectrics for Gate‐Controlled Switchable Rectifier

Abstract: OOP) and in-plane (IP) ferroelectricity could be easily achieved in some atomically thin vdWs 2D ferroelectric films, such as SnTe, CuInP 2 S 6 , LiAlTe 2 , and In 2 Se 3 . [8][9][10][11][12][13][14] Particularly, different from ultrathin SnTe and CuInP 2 S 6 , whose polarization only involves either pure IP or OOP orientations, atomically thin 2D In 2 Se 3 shows both IP and OOP ferroelectricity in its ground state of the α phase. [12] And the IP and OOP polarizations of 2D α-In 2 Se 3 have strong interrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In addition to the Fe-FETs and FTJs, many other useful nanodevices based on the ferroelectric-modulated electron properties are proposed, such as nanorectifiers [97] and nanomemristors. [98]…”
Section: Ferroelectric Tunnel Junctionsmentioning
confidence: 99%
“…In addition to the Fe-FETs and FTJs, many other useful nanodevices based on the ferroelectric-modulated electron properties are proposed, such as nanorectifiers [97] and nanomemristors. [98]…”
Section: Ferroelectric Tunnel Junctionsmentioning
confidence: 99%
“…Figure 2E displays the variations of the clockwise hysteresis window of transfer curves according to the different V bg sweeping range at fixed V sd = 0.2 V. It can be observed that the hysteresis window increases as the maximum V bg increases from 5 to 50 V due to the enhanced IP dipole alignment under large V bg values. 30,[43][44][45] The hysteresis behaviors under both V sd and V bg scans, as discussed above, can provide the potential for this α-In 2 Se 3 device to emulate the synaptic plasticity. To evaluate the essential synaptic behaviors, the device was first measured under V sd pulse (at V g = 0 V), as displayed in Figure 3.…”
Section: Resultsmentioning
confidence: 92%
“…It is worth noting that 100 reversible HRS–LRS switching cycles under the pulse voltage mode can be realized, as shown in Figure S6B, implying good endurance of the device. Figure 2E displays the variations of the clockwise hysteresis window of transfer curves according to the different V bg sweeping range at fixed V sd = 0.2 V. It can be observed that the hysteresis window increases as the maximum V bg increases from 5 to 50 V due to the enhanced IP dipole alignment under large V bg values 30,43–45 …”
Section: Resultsmentioning
confidence: 98%
“…directions, which leads to a zero net IP polarization. When introducing the substrate effect, the threefold rotation symmetry is broken to realize the IP ferroelectricity, which has been well demonstrated in experiment [34,[42][43][44]. Accordingly, both IP and OOP ferroelectricity can be realized in trilayer Bi2Te3.…”
mentioning
confidence: 80%